Does Promotion Orientation Help Explain Why Future-Orientated People Exercise and Eat Healthy? - Milfont, Taciano L.; Vilar, Roosevelt; Araujo, Rafaella C. R.; Stanley, Robert (Frontiers in Psychology, 2017)
A recent study with US undergraduate students showed individuals high in concern with future consequences engage in exercise and healthy eating because they adopt a promotion orientation, which represents the extent to which individuals are inclined to pursue positive gains. The present article reports a cross-cultural replication of the mediation findings with undergraduate samples from Brazil and New Zealand. Promotion orientation mediated the association between concern with future consequences and exercise attitudes in both countries, but the associations for healthy eating were not replicated—which could be explained by distinct obesity prevalence and eating habits in these socio-cultural contexts. We discuss theoretical and practical implications of the findings for promoting health behaviour.